Pharmaceutical attention in the dispensing of antimicrobials, in community pharmacies and drugstores, in the fight against Antimicrobial Resistance - Campos, Jessica Milena Milhomem da Silva; Silva Neto, Antonio Rodrigues da (Research, Society and Development, 2024)
The study aims to investigate the importance of promoting health education by the pharmacist, in the professional/patient relationship, through pharmaceutical attention and care, in community pharmacies and drugstores, in the dispensing of antimicrobials. The study refers to an integrative bibliographic review with searches in databases over the last 10 years (2013-2023) such as Google Scholar, National library of medicine (PubMed) and Scientific Electronic Library Online (SciELO). A total of 10 articles were selected, consisting of 3 from PubMed, 1 from SciELO and 6 from Google Scholar, articles that met the research objectives. In Brazil, around 80 million people practice self-medication. Among the medicines used without professional supervision, antibiotics account for 42% of the total. It was possible to observe the population's lack of knowledge about self-medication with antimicrobials and the consequences, since, in addition to the damage to individual health, they also pose problems to society and the environment. Therefore, the pharmacist, as an enabler of health education, is capable of providing vigilant guidance both for the acquisition and rational use of medicines, and for monitoring the patient's pharmacotherapy.